2020
DOI: 10.3390/land9120513
|View full text |Cite
|
Sign up to set email alerts
|

Does Minimum Tillage Improve Smallholder Farmers’ Welfare? Evidence from Southern Tanzania

Abstract: Conservation agriculture continues to be promoted in developing nations as a sustainable and suitable agricultural practice to enhance smallholder productivity. A look at the literature indicates that this practice is successful in non-African countries. Thus, this research sought to test whether minimum tillage (MT), a subset of conservation agriculture, could lead to a significant impact on smallholder households’ welfare in Southern Tanzania. Using cross-sectional data from 608 randomly selected smallholder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Osewe et al . (2020) studied the impact of MT on the welfare of smallholder farmers in Southern Tanzania. They focused on the effects of MT adoption on households' per capita net crop income and labor demand.…”
Section: Impact Of Ca and Related Technologies Adoption On Welfare Pa...mentioning
confidence: 99%
See 2 more Smart Citations
“…Osewe et al . (2020) studied the impact of MT on the welfare of smallholder farmers in Southern Tanzania. They focused on the effects of MT adoption on households' per capita net crop income and labor demand.…”
Section: Impact Of Ca and Related Technologies Adoption On Welfare Pa...mentioning
confidence: 99%
“…As mentioned earlier in this section, Osewe et al . (2020) found that the adoption of MT in Southern Tanzania had a significant reduction in labor demand thereby affording the household members more time for other non-farm income opportunities. In a similar vein, Johansen et al .…”
Section: Impact Of Ca and Related Technologies Adoption On Welfare Pa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the literature shows an increased weed effect due to minimum tillage [20], but others focus on its benefits [21]. Other literature on the impacts of technology on productivity [20,22,23,24], impact on crop income [19] and impact of practices on farm labor [25,26]. There is also other literature on the impacts of CA on food security [27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Various public policies, such as subsidized prices for seeds and fertilizers, subsidized credit interest and easy access for farmers to sources of financing, have been implemented to encourage food production growth [7]. However, what is still lacking adequate attention is how to maintain the productive capacity of the increasingly limited agricultural land [8,9]. Agricultural land that is cultivated intensively, and ignores the principles of sustainability, will eventually experience degradation.…”
Section: Introductionmentioning
confidence: 99%